2022
DOI: 10.3389/fgene.2022.909007
|View full text |Cite
|
Sign up to set email alerts
|

Cold adaptation strategies in plants—An emerging role of epigenetics and antifreeze proteins to engineer cold resilient plants

Abstract: Cold stress adversely affects plant growth, development, and yield. Also, the spatial and geographical distribution of plant species is influenced by low temperatures. Cold stress includes chilling and/or freezing temperatures, which trigger entirely different plant responses. Freezing tolerance is acquired via the cold acclimation process, which involves prior exposure to non-lethal low temperatures followed by profound alterations in cell membrane rigidity, transcriptome, compatible solutes, pigments and col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 227 publications
0
14
0
Order By: Relevance
“…This association between miR397 and its target genes under cold treatments has been observed in plants including wheat (Gupta et al, 2014) and grapevine (Sun et al, 2015). In addition, miR397 overexpression improved the tolerance to cold stress in Arabidopsis (Dong and Pei, 2014;Satyakam et al, 2022). The core regulator in cold acclimation ICE1 (Chinnusamy et al, 2007) was identified as a target of miR397 in cold adaption in wheat.…”
Section: Molecular Response To Cold Stress In Sorghummentioning
confidence: 73%
See 1 more Smart Citation
“…This association between miR397 and its target genes under cold treatments has been observed in plants including wheat (Gupta et al, 2014) and grapevine (Sun et al, 2015). In addition, miR397 overexpression improved the tolerance to cold stress in Arabidopsis (Dong and Pei, 2014;Satyakam et al, 2022). The core regulator in cold acclimation ICE1 (Chinnusamy et al, 2007) was identified as a target of miR397 in cold adaption in wheat.…”
Section: Molecular Response To Cold Stress In Sorghummentioning
confidence: 73%
“…Some miRNAs participate in plant responses to cold stress (Thiebaut et al, 2012;Liu et al, 2018;Martı ́nez Nu ́ñez et al, 2021;Satyakam et al, 2022). MiR397 is involved in different abiotic stress, including cold (Huang et al, 2020).…”
Section: Molecular Response To Cold Stress In Sorghummentioning
confidence: 99%
“…Cold-responsive genes (CORs) are regulated under CBFs and directly cope with cold stress, with most of these genes encoding late embryogenesis abundant (LEA) proteins ( Fig. 3A ) [ 25 ]. Triplostegia glandulifera had 77 LEA proteins, while L. japonica had 64 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These mechanisms may largely reflect the direct destructive action of thermal stress to cellular components (e.g. denaturation of proteins, cellular membranes and lipids) (Levitt, 1980;Thomashow, 1999;Ruelland & Zachowski, 2010;Narayanan et al, 2016;Tang et al, 2016;Hayes et al, 2021;Zinta et al, 2022). However, secondary mechanisms that damage various cellular and physiological processes (e.g.…”
Section: The Stressful Temperature Rangementioning
confidence: 99%